CARIFESTA XI - 2013 : festival outline; for the CARIFESTA XI Host Country Management Committee (HCMC) Paramaribo, Suriname, 9 December 2012 - Ganga, Sharda (CARIFESTA XI Host Country Management Committee (HCMC) ParamariboSR, 2012)
Outlines the artistic and organisational framework for CARIFESTA XI, to be held in Suriname, 16 -25 August 2013.